Application of method engineering tools to improve the productivity of the production system in the Textil Andes company - Grimaldo Galindez, Angelo Fernando (2022)
This paper on pre-experimental design proposes the application of methods engineering tools, focused on improving the productivity of the Textil Andes company dedicated to the manufacture of ethnic ribbons. By identifying deficiencies and bottlenecks, through the use of the operation process chart and routing diagram, the aim was to reduce the distances and times used, in fact, the processes are unique in the region, therefore it was decided to calculate their standard time which was 250.25 min, and that by implementing a new distribu- tion and working methods it managed to reduce the standard time by 11.65% and the distances used by the product process flow by 49.51%; consequently, a less production time per batch added to the management of a periodic preventive maintenance format, generated a significant decrease in defective units; in other words, the number of good units produced, measured by efficacy, increased by 11.59%. Likewise, the reduction in idle time caused an increase from 89.07 to 94.28% in efficiency, thus achieving an improvement in productivity of 14.77% that directly influences attention and production capacity.